A CRISPR/Cas9‐based method for targeted DNA methylation enables cancer initiation in B lymphocytes. Issue 1 (11th March 2021) - Katayama, Shota; Shiraishi, Koichi; Gorai, Naoki; Andou, Masao
Abstract: Targeted DNA methylation is important for understanding transcriptional modulation and epigenetic diseases. Although CRISPR‐Cas9 has potential for this purpose, it has not yet been successfully used to efficiently introduce DNA methylation and induce epigenetic diseases. We herein developed a new system that enables the replacement of an unmethylated promoter with a methylated promoter through microhomology‐mediated end joining‐based knock‐in. We successfully introduced an approximately 100% DNA methylation ratio at the cancer‐associated gene SP3 in HEK293 cells. Moreover, engineered SP3 promoter hypermethylation led to transcriptional suppression in human B lymphocytes and induced B‐cell lymphoma. Our system provides a promising framework for targeted DNA methylation and cancer initiation through epimutations. Abstract :